SURVEI KEKUATAN OTOT LENGAN ATAS PADA ANAK TUNA GRAHITA DI SLB EKA MANDIRI KOTA BATU - Adharum Krida Marta; Saichudin Saichudin; Rias Gesang Kinanti (Universitas Negeri Malang, 2016)
Abstract :Mental disability is the level of ability of individuals who are not able to adapt to the normal environment and require care, supervision, control and support from outside parties, so it is categorized the development of mental is not perfect. A person who is mental lyretarted can not combinein formationas normal children as generally. So, it need to be give nasimplifiedlesson, instruction that should often be repeated andused short sentences because time of participation in activity is longer.KeyWords:Testmuscle strength and mentally disabled.